2010
DOI: 10.1126/science.1181990
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Sun’s Meridional Flow over a Solar Cycle

Abstract: The Sun's meridional flow is an axisymmetric flow that is generally directed from its equator toward its poles at the surface. The structure and strength of the meridional flow determine both the strength of the Sun's polar magnetic field and the intensity of sunspot cycles. We determine the meridional flow speed of magnetic features on the Sun using data from the Solar and Heliospheric Observatory. The average flow is poleward at all latitudes up to 75 degrees, which suggests that it extends to the poles. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
229
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(265 citation statements)
references
References 23 publications
32
229
1
3
Order By: Relevance
“…The meridional flow results often depend on the method used to derive them, e.g., Doppler measurements, magnetic feature tracking and helioseismic inversions of different kinds (global modes, ring diagrams). Surface Doppler (Ulrich, 2010) and helioseismic (Basu and Antia, 2010) meridional flow measurements generally agree with each other, having peak speeds at low latitudes around 25 ∘ on average, whereas magnetic feature tracking meridional flow measurements (Hathaway and Rightmire, 2010) have much lower values peaking at higher latitudes, around 50 ∘ . Magnetic feature tracking methods give a peak at higher latitudes because they do not separate the bulk fluid flow from the effect of supergranular diffusion.…”
Section: Unusual Cycle 23 Minimumsupporting
confidence: 54%
See 1 more Smart Citation
“…The meridional flow results often depend on the method used to derive them, e.g., Doppler measurements, magnetic feature tracking and helioseismic inversions of different kinds (global modes, ring diagrams). Surface Doppler (Ulrich, 2010) and helioseismic (Basu and Antia, 2010) meridional flow measurements generally agree with each other, having peak speeds at low latitudes around 25 ∘ on average, whereas magnetic feature tracking meridional flow measurements (Hathaway and Rightmire, 2010) have much lower values peaking at higher latitudes, around 50 ∘ . Magnetic feature tracking methods give a peak at higher latitudes because they do not separate the bulk fluid flow from the effect of supergranular diffusion.…”
Section: Unusual Cycle 23 Minimumsupporting
confidence: 54%
“…The meridional flow speed measurements of Ulrich (2010), Basu and Antia (2010) and Hathaway and Rightmire (2011) do not show evidence of significantly faster flows at active latitudes during cycle 23 than during previous cycles. Moreover, Basu and Antia (2010) concluded that the flow speed variation reported by Hathaway and Rightmire (2010) was associated with a flow pattern that migrated equatorward with the magnetic activity belts. When this pattern was removed from their data, the speed variations vanished.…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 99%
“…Furthermore, the tilt angles show a very large scatter, possibly due to the convective buffeting of rising flux tubes in the upper layers of the convection zone (Longcope and Choudhuri 2002). c) meridional flow: significant variability of the meridional flow has been detected during cycle 23 (Chou and Dai 2001;Gizon 2004;Hathaway and Rightmire 2010;González Hernández et al 2010). We considered variations of the meridional flow, of the mean sunspot group tilt angle, and of sunspot number during cycle 23 as potential causes of the low polar field during that cycle and used our SFTM to determine which changes of these properties in cycle 23 would be required to reproduce the observations.…”
Section: Possible Cause Of the Weak Polar Field In Cycle 23mentioning
confidence: 99%
“…However, attempts to measuring the MC velocity using small magnetic structures as tracers of the flow (Komm et al 1993, Hathaway & Rightmire 2010) reveal systematic differences from these results. Compared to Doppler measurements (Ulrich 2010) magnetic feature tracking (MFT) speeds can be as much as ≈ 30% smaller.…”
Section: Introductionmentioning
confidence: 81%